Between digital platforms and investment funds: short-term rental in the age of Financialization - Rodrigues, Larissa Prado (Geografares, 2026)
The article seeks to critically analyze the recent convergence between short-term rental real estate and Real Estate Investment Funds. Although the impacts of “Airbnb-ization” have been widely considered on a global scale in recent decades, there are still few studies investigating how short-term rental sector has emerged as a field of activity for investment funds. In Brazil, a recent trend of this type of financial instrument has been observed expanding into the short-term rental sector. The research is grounded by the dialectical method, seeking to analyze the triadic relationship between tourism, the production of space, and the global processes of the financialization, using the case of Brazilian short-stay FIIs as an empirical reference. The study concludes that this dynamic reflects a trend toward convergence between finance and tourism, revealing a new strategy for the reproduction of financial capital through the financialization of real estate products oriented toward tourism consumption.